ADAPTING TO THE FUTURE OF WORK: SKILLS AND STRATEGIES FOR SUCCESS - Artikov Zokir Sayfiddinovich; Qurbonov Jahongir Ibrohimjonovich (Web of Journals Publishing, 2024)
The future of work is rapidly evolving, driven by technological advancements, globalization, and demographic shifts. This article explores the skills and strategies individuals and organizations need to adapt and thrive in this changing landscape. It examines emerging trends such as remote work, automation, and the gig economy, and their impact on employment dynamics. Additionally, it delves into the importance of lifelong learning, adaptability, and resilience in navigating the future of work. By embracing a growth mindset, cultivating transferable skills, and leveraging technology, individuals and organizations can position themselves for success in an increasingly competitive and dynamic work environment.
Keywords: future of work, skills, strategies, remote work, automation, gig economy, lifelong learning, adaptability, resilience, technology.